Superoxide and Non-ionotropic Signaling in Neuronal Excitotoxicity - Wang, Jiejie; Swanson, Raymond A. (Frontiers in Neuroscience, 2020)
Excitotoxicity is classically attributed to Ca2+ influx through NMDA receptors (NMDAr), leading to production of nitric oxide and mitochondrial superoxide, which together generate the cytotoxic peroxynitrite radical. More recent observations warrant revision of the classic view and help to explain some otherwise puzzling aspects of excitotoxic cell injury. Studies using pharmacological and genetic approaches show that superoxide production induced by NMDAr activation originates primarily from NADPH oxidase rather than from mitochondria. NADPH oxidase is localized to the plasma membrane, and release of superoxide to the extracellular space thereby provides a mechanism for the cell-to-cell “spread” of excitotoxic injury observed in vitro and in vivo. The signaling pathway linking NMDAr to NADPH oxidase involves Ca2+ influx, phosphoinostitol-3-kinase, and protein kinase Cζ, and interventions at any of these steps prevents superoxide production and excitotoxic injury. Ca2+ influx specifically through NMDAr is normally required to induce excitotoxicity, through a mechanism presumed to involve privileged Ca2+ access to local signaling domains. However, experiments using selective blockade of the NMDAr ion channel and artificial reconstitution of Ca2+ by other routes indicate that these special effects of NMDAr - mediated Ca2+ influx are attributable instead to the concurrent action of non-ionotropic NMDAr signaling during agonist binding to NMDAr. The non-ionotropic signaling is mediated by the C-terminal domain of GluN2B receptor subunits, and is associated with phosphoinostitol-3-kinase binding to GluN2B. These more recently identified aspects of excitotoxicity expand our appreciation of the complexity of excitotoxic processes and suggest novel approaches for limiting neuronal injury.